2018
DOI: 10.1177/1359105318770729
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a physical activity program on post-bariatric patients: A qualitative study from a self-determination theory perspective

Abstract: This study provides an in-depth analysis of the psychosocial benefits that 10 post-bariatric patients (nine female, 31-59 years) perceived from their participation in an exercise program grounded in self-determination theory. Qualitative data were collected through observations and interviews. Participants reported many factors which facilitated basic psychological need satisfaction such as the instructors caring about their opinion, affection, fitness improvement, pain reduction, and knowledge acquisition. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…According to SDT, if basic psychological needs are satisfied in social contexts, people tend to be more autonomously motivated for the maintenance of healthy behaviours and their psychological wellbeing tends to improve (Ryan & Deci, 2017). A previous study derived from our research project showed that a PA program based in SDT can promote, in bariatric patients, enjoyment, happiness, self-confidence, motivation and intention to be physically active in the future (González-Cutre, Megías, Beltrán-Carrillo, Cervelló, & Spray, 2018).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…According to SDT, if basic psychological needs are satisfied in social contexts, people tend to be more autonomously motivated for the maintenance of healthy behaviours and their psychological wellbeing tends to improve (Ryan & Deci, 2017). A previous study derived from our research project showed that a PA program based in SDT can promote, in bariatric patients, enjoyment, happiness, self-confidence, motivation and intention to be physically active in the future (González-Cutre, Megías, Beltrán-Carrillo, Cervelló, & Spray, 2018).…”
Section: Introductionmentioning
confidence: 88%
“…The programme consisted of two sessions per week during the first two months, three sessions per week during the intermediate two months, and four sessions per week during the last two months, each lasting 1 hour and 30 minutes. More information about the PA programme can be found in González-Cutre et al (2018).…”
Section: Procedures and Interview Protocolmentioning
confidence: 99%
“…As indicated in the quote above there is a need for qualitative psychological studies with a clear theoretical framework aiming to explore obese individuals’ perception of the weight loss maintenance process. Recently examples of such studies have been published with self-determination theory (SDT) as their framework (Donnachie et al , 2017; González-Cutre et al , 2018). Such studies have the potential to empirically inform both theoretical development and practical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the difficulties in weight loss and maintenance are closely related to the difficulties in changing habits and life style (González-Cutre et al, 2018;Latner & Ciao, 2013), there are some endoscopic approaches aimed at correcting the GJA dilation. Argon Plasma Coagulation (APC) is an electrocoagulation method that uses an injection of ionized gas into the tissue.…”
mentioning
confidence: 99%
“…For surgical procedures to be successful, they must be combined with other forms of professional support for operated patients. Only physiological change has been shown to be inefficient in an important percentage of patients, which indicates that other variables need to be considered (González-Cutre et al, 2018;Vuuren et al, 2016). In cases of weight relapse, it is important to understand the associated psychological and social aspects, considering that food and eating habits are social and cultural constructions that go beyond the physiological component (LoMonaco & Bonetto, 2019).…”
mentioning
confidence: 99%